2022
DOI: 10.2147/dmso.s370017
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hyperglycemia on the Prognosis of Patients with Diffuse Large B-Cell Lymphoma

Abstract: Purpose To explore the effects of primary and secondary hyperglycemia and the application of the hypoglycemic drug metformin on the prognosis of patients with diffuse large B-cell lymphoma (DLBCL). Methods We performed a retrospective analysis of 1767 DLBCL patients.Cox regression method was used for analysis to evaluate the prognostic factors, and the Kaplan-Meier method was used to draw a survival curve to analyze the effect of hyperglycemia and the hypoglycemic drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Another study by Zhou et al, likewise shows a reduction in PFS and OS in subjects who develop steroid-induced hyperglycemia in the context of therapy with R-CHOP for DLBCL. Of note, the study by Zhou et al, also suggests that the adverse effects of steroid-induced hyperglycemia on PFS and OS can be mitigated with the use of metformin [5]. The objective of our study was to characterize the effect of steroid-induced hyperglycemia on outcomes of R-CHOP chemotherapy for individuals diagnosed with diffuse large B-cell lymphoma (DLBCL) in Manitoba, Canada.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study by Zhou et al, likewise shows a reduction in PFS and OS in subjects who develop steroid-induced hyperglycemia in the context of therapy with R-CHOP for DLBCL. Of note, the study by Zhou et al, also suggests that the adverse effects of steroid-induced hyperglycemia on PFS and OS can be mitigated with the use of metformin [5]. The objective of our study was to characterize the effect of steroid-induced hyperglycemia on outcomes of R-CHOP chemotherapy for individuals diagnosed with diffuse large B-cell lymphoma (DLBCL) in Manitoba, Canada.…”
Section: Introductionmentioning
confidence: 99%
“…The high doses of steroids used in chemotherapy regimens for the treatment of leukemias, lymphomas, and multiple myeloma can prove especially problematic in this regard. Steroidinduced hyperglycemia has been associated with an increase in treatment-related toxicities including neutropenia, infection/sepsis [2,4,5], and chemotherapy-related neuropathies [6]. Associations have also been documented between steroid-induced hyperglycemia and a greater risk of failing to complete the intended course of chemotherapy, early disease relapse, and decreased overall survival [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Current studies have shown that diabetes is an important risk factor for DLBCL, significantly shortening survival time and increasing the risk of death. 4 - 6 Insulin-like growth factor 2mRNA–binding protein 2 (IGF2BP2), which is located on chromosome 3 (3q27.2), is also associated with a higher risk of death. In combination with insulin-like growth factor 2mRNA, it can affect cell differentiation, proliferation, and epigenetic inheritance in various ways, playing a significant role in the development and occurrence of cancer.…”
Section: Introductionmentioning
confidence: 99%